Achieving complete remission in metastatic hepatocellular carcinoma with sintilimab plus sorafenib therapy followed by hepatic resection: a case report - Cui, Kai; Li, Zhongchao; Zhong, Jingtao; Shi, Xuetao; Zhao, Lei; Li, Hao; Ma, Ying (Frontiers in Oncology, 2024)
The synergistic effectiveness of combining immune checkpoint inhibitors with targeted therapies has shown promise in improving the conversion rate for unresectable hepatocellular carcinoma (HCC) patients to a potentially resectable status. However, the efficacy of this approach in the context of HCC with extrahepatic metastasis remains to be conclusively determined.We report a rare case of advanced HCC with extrahepatic metastasis who achieved long-term survival by a combination of systemic therapy (sintilimab and sorafenib) followed by laparoscopic hepatectomy. A 63-year-old man presented at our hospital with discomfort on the right side of his waist. An enlarged right hepatic lobe mass was subsequently revealed by CT scan. The patient's medical history, including a prior infection with hepatitis B virus, cirrhosis of the liver and an alpha-fetoprotein (AFP) level measuring 41.28 ng/ml substantiated the clinical diagnosis of HCC. On October 30th, 2019, the patient received 200 mg sintilimab intravenously (q3w) plus 200-400 mg BID sorafenib orally, along with antiviral therapy. After six cycles, his disease achieved partial response (PR). On April 26th, 2021, He underwent a laparoscopic hepatectomy. The patient achieved a sustained period of no evidence of disease for 2.5 years and with drug-free survival for 2 years after the resection. His current overall survival is estimated at approximately 4 years.This case highlights the potential of combining sintilimab and sorafenib in transforming HCC with extrahepatic metastasis into a condition amenable to surgical resection, suggesting that this treatment approach, followed by surgery, may lead to complete remission.